KEMAMPUAN MAHASISWA CALON GURU MENERAPKAN PENILAIAN KINERJA UNTUK MENILAI HASIL BELAJAR SISWA DALAM PEMBELAJARAN MATEMATIKA - Hifzi Meutia (Jurnal Peluang, 2012)
Abstrac            Performance assessment is one of alternative assessment that not only assess the final outcome but also assess the processes and skills of students in solving the task. This study aimed to analyze the pre-service teachers’ ability to create and use rubrics in assess students’ performance. Data collected through observation, interviews, and documentation. We used two scoring rubrics, to assess the pre-service teachers’s ability in designed and use their rubrics. The result are: 1) the ability of pre-service teachers in designing the assessment rubric for first meeting indicate that all subject has a good skill level, next up for the second meeting of the subject A has a very good skill level, subject B and subject D has a good skill level, while subject C has a pretty good skill level. 2) the ability of pre-service teachers in using assessment rubric for first meeting indicate that the subject A, subject C, and subject D each subject has a very good skill level, while subject B has a good skill level, next up for the second meeting of subject A, subject B, and subject D each subject has a very good skill level, while subject C has a good skill level.Keyword: Performance assessment, scoring rubric, pre-service teachers, ability to designed and used their rubrics.